Potential benefits of vitamin D for sepsis prophylaxis in critical ill patients - Guan, Jianbin; Shichen, Maoyou; Liang, Zhihui; Yu, Shuang; Zhao, Min; Zhang, Lu; Lv, Ronggui; Liu, Yong; Chang, Ping; Liu, Zhanguo (Frontiers in Nutrition, 2023)
Background: Vitamin D deficiency is common in critically ill patients with suspected infection and is strongly associated with the predisposition of sepsis and a poor prognosis. The effectiveness of vitamin D supplementation for preventing sepsis remains unclear. This retrospective cohort study investigated the effect of vitamin D supplementation on sepsis prophylaxis in critically ill patients with suspected infection. Methods: This retrospective cohort study included 19816 adult patients with suspected infection in intensive care units (ICU) from 2008 to 2019 at the Beth Israel Deaconess Medical Center, Boston, USA. The included patients were divided into the vitamin D cohort or non-vitamin D cohort according to vitamin D administration status. The primary outcomes were the incidence of sepsis in ICU. The secondary outcomes included 28-day all-cause mortality, length of ICU and hospital stay and the requirements of vasopressors or mechanical ventilation. A propensity score matching cohort was used to test the differences in primary and secondary outcomes between groups. Results: The results showed that vitamin D supplementation demonstrated a lower risk of sepsis (odd ratio 0.46; 95% CI 0.35–0.60; P < 0.001) and a lower risk of new mechanical ventilation requirement (odd ratio 0.70; 95% CI 0.53-0.92; P = 0.01), but no significant difference in the risk of 28-day mortality was observed (hazard ratio 1.02; 95% CI 0.77–1.35; P = 0.89).In the sensitive analysis, among the patients who suspected infection within 24h before or after ICU admission, a lower risk of sepsis and a lower percentage of new mechanical ventilation also were detected in the vitamin D cohort. Conclusion: vitamin D supplementation may have a positively prophylactic effect on sepsis in critically ill patients with suspected infection.